The use of magnetic-laser therapy of patients with post-dental implant neuropathy - Hakobyan Gagik; Lazar Yesayan; Arman Seyranyan; Davit Matevosyan (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2020)
Objective: The aim of this study was to assess the effectiveness of magnetic-laser therapy in complex treatment of neuropathy after dental implantation Materials and methods: The present study is based on the results of the analysis of clinical, instrumental and radiation studies of 27 patients, with post-traumatic neuropathy inferior alveolar nerve. Diagnosis of damage to the inferior alveolar nerve was based on the clinical manifestations of neuropathy (pain, paresthesia, loss of sensation, etc.). The study of the sensitivity of the skin of the lower lip and chin in the segment of the inferior alveolar nerve dysfunction and in the symmetrical segment performed using sensory tests.  Conservative treatment included: Anti-inflammatory, analgesics, antioxidants, B complex of the vitamins group. Magnetic-laser therapy included in a conservative treatment complex for patients.  To conduct a comparative analysis of effectiveness of magnetic-laser therapy, two groups were formed: Patients first group (n= 14), whose treatment complex included magnetic- laser therapy, Patients second group (n= 13), whose treatment complex did not include magnetic-laser therapy. Results: Most patients after implant placement complained of pain of varying degrees, a decrease or lack of sensitivity of the lower lip, chin skin, and the mucous membrane of the alveolar process of the lower jaw, paresthesia or hyperesthesia. Some patients did not have pain, however noted that sensitivity disorders have a negative effect on general well-being and interfere with work. When comparing 2 group the best pain relief was patients first group. The average area of skins sensory impairment in patients was mean 9.4cm2. Patients first group complete recovered function of inferior alveolar nerve within mild 1 month, patients in the second group, whose treatment complex did not include magnetic laser therapy, fully recovered function of inferior alveolar nerve within mild 2 months. Conclusion: Thus, the inclusion of magnetic laser therapy in the post-implantation traumatic neuropathy treatment complex allows to reduce the recovery time of functional disorders of the inferior alveolar nerve, to reduce the area of skins sensory impairment and increase the effectiveness of treatment.